Deutsche Gründungsmythen: Schlachten, Fußball und die staatliche Einheit. Kleist – Wortmann – Reitz - Preusser, Heinz-Peter (Revista de Filología Alemana, 2007)
Foundational narratives are used for legitimatory purposes. They produce meaning and offer orientation and perspectives through which the contingency of historical trajectories is obscured and the complexity of economic, social and political processes is reduced. On the one hand, these narratives contribute to the enlightenment aspect of all myth production: the desire for orientation, for comprehension and processing of the world. On the other hand, they transfigure because they produce false syntheses. German history with its discontinuities and ruptures is characterised by a persistent desire for myth. Myth fictionalises historical events in the attempt to heal the rifts, to conjure up and simultaneously produce the unity that never was. Foundational myths thus compensate a lack of ‘unquestionable’ – national – identity. Many of the German foundational myths became influential during and after the repeated struggles for national unity.